Formation and transformation of Georgian pop culture (television, radio) - Giorgi Abazadze (Scientific Research and Experimental Development, 2025)
This article examines the role of Georgian television and radio in the formation and dissemination of local pop culture. The issue is considered from the perspective of the study of culture, media and identity, based on the analysis of both historical and contemporary processes. The aim of the article is to show how Georgian media (especially television and radio) have become agents of cultural transformation in the post-Soviet space. The text is based on both a theoretical framework and specific empirical examples. Mass media and pop culture shape public memory, identity, and the worldview of the younger generation. Georgian media has many unique characteristics – both due to its historical baggage and post-Soviet transformation